Magnetic properties of Yb(Rh0.42Co0.58)2Si2. Issue 3 (18th February 2013) - Hannaske, Ariane; Stockert, Oliver; Klingner, Christoph; Krellner, Cornelius; Matas, Slavomir; Pedrero, Luis; Brando, Manuel; Geibel, Christoph; Steglich, Frank
Abstract In this paper, we present a comprehensive study of heat capacity, resistivity, neutron diffraction and magnetization measurements on Yb(Rh0.42Co0.58)2Si2. Heat capacity and resistivity measurements revealed one phase transition at Tm ≈ 820 mK into the magnetically ordered phase, but in neutron diffraction experiments the magnetic intensity at the commensurate position <![CDATA[τ = ( 0.25 & 0.75 & 0 )]]> <inline-graphic xlink:href="ark:/27927/pgg1v77r9gv" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> vanished already at a lower TL ≈ 700 mK. From magnetization measurements we could derive the existence of two magnetic phases, an antiferromagnetic phase below TL ≈ 700 mK and an intermediate phase in the temperature range <![CDATA[T_L < T < T_m ]]> <inline-graphic xlink:href="ark:/27927/pgg1v77r9c6" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, which shows surprisingly ferromagnetic properties when applying magnetic fields along the [001] direction.